3D/4D breast ultrasound - Weismann, Christian (Radiology and oncology (Ljubljana), 2004)
Background. Three-dimensional (3D) and four dimensional(4D) mammasonography isthe most recent development in breast ultrasound imaging providing additional aspects to conventional two-dimensional (2D) sonography. Conclusions. The new technique of mammasonography enable completely new superior diagnostic information such as the ability to study a breast mass andthe surrounding tissue in 3 orthogonal planes, or to obtain new informationabout the mean blood flow intensity or vascularisation of breast lesions by evaluation of the 3D colour histogram. 4D ultrasound offers almost real time 3D rendered image information and is taken as a basis of multidimensional imaging of the breast.
Keywords: Breast Neoplasms; diagnostika; Dojka, novotvorbe; dojke; mamografija; rak (medicina); Ultrasonografija dopplerska; Ultrasonography; Ultrasonography, Doppler